2007
DOI: 10.7326/0003-4819-146-5-200703060-00006
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-analysis: New Tests for the Diagnosis of Latent Tuberculosis Infection: Areas of Uncertainty and Recommendations for Research

Abstract: New IGRAs show considerable promise and have excellent specificity. Additional studies are needed to better define their performance in high-risk populations and in serial testing. Longitudinal studies are needed to define the predictive value of IGRAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
686
6
60

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 907 publications
(782 citation statements)
references
References 70 publications
30
686
6
60
Order By: Relevance
“…In previous meta-analyses, similarly to data reported in adults, higher IGRA specificity with respect to TST has been reported. However, the reported IGRA sensitivity ranged between 62% and 89% for T-SPOT.TB and 66% and 83% for QFT-G-IT [1,5,9-11]. Differences between IGRA performance in low income and high income countries were evaluated only in one meta-analysis which considered only QFT-G-IT- (and not T-SPOT.TB-) based studies [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous meta-analyses, similarly to data reported in adults, higher IGRA specificity with respect to TST has been reported. However, the reported IGRA sensitivity ranged between 62% and 89% for T-SPOT.TB and 66% and 83% for QFT-G-IT [1,5,9-11]. Differences between IGRA performance in low income and high income countries were evaluated only in one meta-analysis which considered only QFT-G-IT- (and not T-SPOT.TB-) based studies [1].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported a sub-optimal IGRA sensitivity in children [14], but this finding has not been confirmed by others [8]. Five meta-analyses have previously assessed IGRA sensitivity and specificity in children but reported pooled estimates largely differ (Table 1) [1,5,9-11]. Such discordances may be due to different inclusion/exclusion criteria and, thus, different characteristics of the study populations (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the general population, these 2 tests have good concordance for detecting latent TB. 11 One study compared QFT to PPD testing in 153 chronic liver disease patients awaiting liver transplantation. Concordance between the 2 tests was 85.1% (k ¼ 0.60), and this suggests that QFT was comparable to PPD for the diagnosis of latent TB in this population.…”
Section: Diagnosis Latent Tbmentioning
confidence: 99%
“…[14][15][16] Because both QFT and TST measure the cellular immune response to M. tuberculosis, testing with QFT is unlikely to be helpful in patients with a negative TST related to defective cellular immune responses. 11,12 The full evaluation of a patient with cirrhosis before liver transplantation should be thorough and include a detailed medical and exposure history and a review of chest radiography (see the section on the evaluation of transplant candidates and donors). In posttransplant recipients, the diagnosis of LTBI similarly involves the use of TST or interferon-c release assay testing.…”
Section: Diagnosis Latent Tbmentioning
confidence: 99%